Contribuciones del intercambio virtual al desarrollo de competencias interculturales: Una perspectiva de las instituciones de educación superior brasileñas - Zilberberg Oviedo, Lourdes Evangelina; Krimphove, Jan (Universidad de Costa Rica, 2022)
This article presents the results of a study conducted in the Brazilian higher education system aiming at analyzing the contributions of virtual exchange programs to the development of intercultural competence in students. The unprecedented study assists to enrich the limited body of knowledge about virtual exchanges in Brazil. The units of analysis consisted of member institutions of the Brazilian Association for International Education (FAUBAI) that were already running virtual exchange programs in 2020. The study follows an exploratory qualitative research approach based on semi-structured interviews with international office administrators of the institutions analyzed. What stands out among the study’s main findings is the fact that, Brazilian international office administrators consider virtual exchanges as an important tool for Internationalization at Home, and thus, a path toward a more inclusive internationalization model. Even with all the difficulties, such as: major technical issues, low level of language proficiency in faculty and students, lack of commitment and the disadvantages deriving from lack of a deeper and more intense cultural immersion when compared to real-life experiences, there is a consensus that virtual exchanges do contribute toward the development of intercultural competence in students. Therefore, it seems important to promote more Internationalization at Home initiatives to create more circumstances of proximity with other cultures and second-language learning opportunities.